A Study to Analyze the Impact of Knowledge Management (KM) practices in IT Service Delivery Industry in India - et. al., Barakath Ali Shaik Mohamed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Information Technology (IT) Industry in India is growing fast. Organizations across the world are outsourcing the IT services to take advantage of cost and time differences. India plays vital role in supporting the outsourcing services by taking advantage of the language skills and skilled workforce. Knowledge Management (KM) is critical for the continuity of the services and success of the organisations in different domains. This paper analysis the impact of Knowledge Management in Information Technology (IT) Service Delivery Industry in India. The study reveals Knowledge Management improves the performance of the Service Delivery organization. Methodical implementation and continuous improvement of Knowledge Management practices would further accelerate and improve the customer experience.